Die königlichen Amduat-Fragmente vor der Regierungszeit Thutmosis’ III - Ghany, Khaled Abdel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
After thorough comparative examination of the Amduat limestone fragments from the tombs of king Thutmose I (KV38) and queen Hatshepsut (KV20), it is my conclusion that these limestone fragments of the oldest and earliest version of the Amduat Book together are forming an entity, that this is actually one single specimen. Therefore I assume that all fragments originate from only one tomb, namely from Thutmose I (KV 38), and neither from two different tombs nor from different reigns. It therefore seems problematic to state that any of these fragments might originate from tomb KV 20. Moreover, after having discovered the earliest ever mud-plaster fragments of the Amduat Book in the tomb of Thutmose I (KV 38) in the Valley of Kings, I could prove that the Amduat Book was already known during the reign of Thutmose I.